Liver disease accompanied by enteropathy in common variable immunodeficiency: Common pathophysiological mechanisms - Lima, Fabiana Mascarenhas Souza; Toledo-Barros, Myrthes; Alves, Venâncio Avancini Ferreira; Duarte, Maria Irma Seixas; Takakura, Cleusa; Bernardes-Silva, Carlos Felipe; Marinho, Ana Karolina Barreto Berselli; Grecco, Octavio; Kalil, Jorge; Kokron, Cristina Maria (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID) is one of the inborn errors of immunity that have the greatest clinical impact. Rates of morbidity and mortality are higher in patients with CVID who develop liver disease than in those who do not. The main liver disorder in CVID is nodular regenerative hyperplasia (NRH), the cause of which remains unclear and for which there is as yet no treatment. The etiology of liver disease in CVID is determined by analyzing the liver injury and the associated conditions. The objective of this study was to compare CVID patients with and without liver–spleen axis abnormalities in terms of clinical characteristics, as well as to analyze liver and duodenal biopsies from those with portal hypertension (PH), to elucidate the pathophysiology of liver injury. Patients were divided into three groups: those with liver disease/PH; those with isolated splenomegaly; and those without liver–spleen axis abnormalities. Clinical and biochemical data were collected. Among 141 CVID patients, 46 (32.6%) had liver disease/PH; 27 (19.1%) had isolated splenomegaly; and 68 (48.2%) had no liver–spleen axis abnormalities. Among the liver disease/PH group, patients, even those with mild or no biochemical changes had clinical manifestations of PH, mainly splenomegaly, thrombocytopenia, and esophageal varices. Duodenal celiac pattern was found to correlate with PH (p < 0.001). We identified NRH in the livers of all patients with PH (n = 11). Lymphocytic infiltration into the duodenal mucosa also correlated with PH. Electron microscopy of liver biopsy specimens showed varying degrees of lymphocytic infiltration and hepatocyte degeneration, which is a probable mechanism of lymphocyte-mediated cytotoxicity against hepatocytes and enterocytes. In comparison with the CVID patients without PH, those with PH were more likely to have lymphadenopathy (p < 0.001), elevated β2-microglobulin (p < 0.001), low B-lymphocyte counts (p < 0.05), and low natural killer-lymphocyte counts (p < 0.05). In CVID patients, liver disease/PH is common and regular imaging follow-up is necessary. These patients have a distinct immunological phenotype that may predispose to liver and duodenal injury from lymphocyte-mediated cytotoxicity. Further studies could elucidate the cause of this immune-mediated mechanism and its treatment options.